Kilohertz electrical stimulation evokes robust cellular responses like conventional frequencies but distinct population dynamics - Cara R. Ravasio; Krishnakanth Kondabolu; Samuel Zhou; Eric Lowet; Erynne San Antonio; Rebecca A. Mount; Sukhneet K. Bhogal; Xue Han (Communications Biology)
Abstract Intracranial electrical kilohertz stimulation has recently been shown to achieve similar therapeutic benefit as conventional frequencies around 140 Hz. However, it is unknown how kilohertz stimulation influences neural activity in the mammalian brain. Using cellular calcium imaging in awake mice, we demonstrate that intracranial stimulation at 1 kHz evokes robust responses in many individual neurons, comparable to those induced by conventional 40 and 140 Hz stimulation in both the hippocampus and sensorimotor cortex. The evoked responses at the single-cell level are shaped by prominent network inhibition and critically depend on brain region. At the network level, all frequencies lead to pronounced population suppression except 1 kHz in the cortex, which evokes balanced excitatory and inhibitory population effects. Thus, kilohertz stimulation robustly modulates neural activity at both the single-neuron and population network levels through mechanisms distinct from conventional frequency stimulation, highlighting the clinical potential of intracranial kilohertz neuromodulation.